Improving the Privacy of IoT with Decentralised Identifiers (DIDs) - Kortesniemi, Yki; Lagutin, Dmitrij; Elo, Tommi; Fotiou, Nikos (Journal of Computer Networks and Communications, 2019)
When IoT devices operate not only with the owner of the device but also with third parties, identifying the device using a permanent identifier, e.g., a hardware identifier, can present privacy problems due to the identifier facilitating tracking and correlation attacks. A changeable identifier can be used to reduce the risk on privacy. This paper looks at using decentralised identifiers (DIDs), an upcoming standard of self-sovereign identifiers with multiple competing implementations, with IoT devices. The paper analyses the resource requirements of running DIDs on the IoT devices and finds that even quite small devices can successfully deploy DIDs and proposes that the most constrained devices could rely on a proxy approach. Finally, the privacy benefits and limitations of using DIDs are analysed, with the conclusion that DIDs significantly improve the users’ privacy when utilised properly.